THE EFFECTIVENESS OF ACUPRESSURE THERAPY FOR DYSMENORRHEA IN ADOLESCENT GIRLS - Ardiyanti Hidayah; Rista Dian Anggraini; Siti Nur Farida (Literasi Kesehatan Husada)
Background: Dysmenorrhea is pain during menstruation. There are 2 types of dysmenorrhea, namely primary dysmenorrhoea and secondary dysmenorrhoea. Primary dysmenorrhea is dysmenorrhea without any abnormalities in the genital organs. Secondary dysmenorrhea is dysmenorrhea in the presence of abnormalities in the genital organs, such as tumors, inflammation, etc. Acupressure is a development of massage therapy pressing on acupuncture points which increases oxygen saturation and causes muscle relaxation effects.